I Comuni cittadini italiani (Heidelberg University Publishing (heiUP), 2026)
The volume combines recent research trends, investigating the Italian city communes in light of the key concepts „actors“, „artifacts“, and „processes“. These analytical categories specifically address newly emerging and particularly dynamic research approaches, offering a novel perspective on the development of the commune. By revealing previously overlooked interdependencies and areas of interaction, as well as hitherto neglected communication channels and transformations, the contributions enable a better understanding of relational networks and the evolution of daily life within the communes.